Pelatihan Wawancara Penyidikan Ramah Anak Berbasis NICHD Versi 2007 bagi Penyidik Polri dalam Proses Pembuatan Berita Acara Pemeriksaan Anak-Anak - , PUTRI MARLENNY PUSPITAWATI, Prof. Dr. Endang Ekowarni, Psi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The testimony of a child victim of sexual assault, when he/she was in the police station, could become important initial information in search of initial evidence for the filing of criminal proceedings. Immature cognition and psychological distress in children, who allegedly suffered sexual abuse, can pose difficulties for Indonesian police investigators in the process of investigative interview. Therefore, an effective yet emphatic investigative interview technique is required for underage victims of sexual assault. This study examined the effectiveness of Child Friendly âRamah Anakâ based on the 2007 version National Institute of Child Health and Human Development (NICHD) Investigative Interview Training Program enhances the police investigatorsâ emphatic investigative interview skill in dealing with children of 4-13 years old who allegedly sexually assaulted. Subjects were police investigators (Criminal Investigator of Women and Children Protection Unit). Design used in this study was a post-test only design with non-equivalent group. Measurements (post-test) were conducted on two groups, experimental and control groups by use of observation check-list. The result of U Mann-Whitney indicated that emphatic investigative interview skill in the experimental group had a mean rating of 6.60, higher than that of the control group (mean = 4.40), which p=0,008 (p<0,05). It means that the program was effective in enhancing emphatic investigative interview skill.